2015
DOI: 10.1021/acsami.5b08419
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Collagen/Glycosaminoglycan-Based Cellular Microenvironments for Tuning Osteoclastogenesis

Abstract: Replicating the biocomplexity of native extracellular matrices (ECM) is critical for a deeper understanding of biochemical signals influencing bone homeostasis. This will foster the development of bioinspired biomaterials with adjustable bone-inducing properties. Collagen-based coatings containing single HA derivatives have previously been reported to promote osteogenic differentiation and modulate osteoclastogenesis and resorption depending on their sulfation degree. However, the potential impact of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 60 publications
1
37
0
1
Order By: Relevance
“…A degraded, low-molecular weight HA, was prepared as previously described to serve as reference material for in vitro experiments since the molecular weight of natural HA precursor is decreased during sulfation45545556 HA derivatives with a degree of sulfation (D.S., number of sulfate residues per disaccharide unit) of 1.0–1.5 referred to as low-sulfated HA derivative sHA1 (Table 1). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A degraded, low-molecular weight HA, was prepared as previously described to serve as reference material for in vitro experiments since the molecular weight of natural HA precursor is decreased during sulfation45545556 HA derivatives with a degree of sulfation (D.S., number of sulfate residues per disaccharide unit) of 1.0–1.5 referred to as low-sulfated HA derivative sHA1 (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…7, Table 1)5657. The double-labeled ATTO565-ATTO655-sHA1 derivative was prepared by coupling ATTO565-NH 2 to the reducing end of sHA1 via an azomethine bond and subsequent reduction of the C=N double bond (end-on functionalization), followed by coupling of ATTO655-NH 2 at the carboxyl group of the GAG using EDC/NHS (1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide/N-hydroxy succinimide).…”
Section: Methodsmentioning
confidence: 99%
“…In mixtures of collagen and hyaluronic acid, it was found that additions of sulphate groups to the hyaluronic acid led to a decrease in fiber size after fibrillogenesis. 54 The extra sulphation also correlated to a decrease in osteoclastogenesis. 54 However, organic materials are not the only molecules which can be incorporated into growing collagen fibers.…”
Section: Harnessing Collagen's Potentialmentioning
confidence: 97%
“…37,39 These molecules can be incorporated into growing fibrils during in vitro fibrillogenesis, and their properties influence the final structure. 54 In mixtures of collagen and hyaluronic acid, it was found that the sulphation state of the GAG altered the isoelectric point of the final gels formed, and higher sulphation decreased the fibril size. 54 Silicates can also can interact with collagen fibrils to control nucleation.…”
Section: Building a Network: Collagen Fibrillogenesismentioning
confidence: 99%
See 1 more Smart Citation